Drug Preventization, Curative and Rehabilitation in Islamic Psychology - Mardalena, Rilta; Vivik Shofiah; Khairunnas Rajab (STAI Terpadu Yogyakarta, 2025)
The suitability of prevention, and curatitation, rehabilitation patterns and techniques given to drug addicts must be appropriate to the patient's condition, including cultural factors where the individual lives, in the context of its application in Indonesia, where the majority of the population is Muslim. Basically, the process and techniques for coaching drug addicts are important in increasing understanding, appreciation and use of Islamic values in all aspects of life. Where a drug addict is someone who experiences mental disorders, a sick person, a patient, who needs therapeutic help and rehabilitation and not punishment. The aim of the research is to determine the effectiveness of prevention, curatization and rehabilitation of drug addicts from an Islamic psychology perspective. The method in this research, namely systematic literature review, is a process used to study, evaluate and interpret all existing research that is relevant to the formulation of the problem or topic being studied. The results of this research show that a preventive, curatization and rehabilitation approach for drug addicts has a good effect on the progress of their rehabilitation